Interleukin 6 Function in the Skin and Isolated Keratinocytes Is Modulated by Hyperglycemia - Eric G. Lee; Lerin R. Luckett-Chastain; Kaitlin N. Calhoun; Benjamin Frempah; Anja Bastian; Randle M. Gallucci (Journal of Immunology Research)
Diabetes currently affects over twenty-five million Americans. Annual health care cost of diabetes exceeds $254 billion and is associated with a distinct set of diabetic complications that include delayed wound healing and diabetic ulcers. Interleukin 6 (IL-6) plays an important role in wound healing and is known to be elevated in the serum of both type I and type II diabetes patients. This study assesses the expression and function of IL-6 in the hyperglycemic epidermis and keratinocyte culture. Streptozotocin-treated mice were wounded six weeks after induction of hyperglycemia. Wound closure, protein, and mRNA expression were assessed up to 13 days of postwounding. Wound closure was delayed 4-5 days in hyperglycemic animals. Hyperglycemic wounds displayed greater IL-6 and IL-6Rα protein expression at 1, 7, and 10 days of postwounding compared to euglycemic control. However, IL-6Rα mRNA expression was reduced at all time points beyond day 1, while IL-6 mRNA expression did not significantly differ at any time point. SOCS3 mRNA expression was higher in the hyperglycemic skin at every time point. Imaging of fluorescent immunohistology also revealed significantly lower expression of SOCS3, but higher nuclear pSTAT3 in the epidermis of the hyperglycemic skin. Primary mouse keratinocytes cultured in high glucose for 7 days displayed 2-fold higher IL-6Rα mRNA and higher rmIL-6-induced nuclear pSTAT3, but lower SOCS3 basal levels compared to normal glucose-cultured cells. Thus, it appears that delayed diabetic skin wound healing is associated with increased induction and expression of IL-6 and its receptor, but its function in epidermal keratinocytes may be impaired.